Echocardiographic assessment of Xenopus tropicalis heart regeneration - Luocheng Lv; Weimin Guo; Wei Guan; Yilin Chen; Ruijin Huang; Ziqiang Yuan; Qin Pu; Shanshan Feng; Xin Zheng; Yanmei Li; Luanjuan Xiao; Hui Zhao; et al. (Cell & Bioscience, 2023)
Abstract Background Recently, it was reported that the adult X. tropicalis heart can regenerate in a nearly scar-free manner after injury via apical resection. Thus, a cardiac regeneration model in adult X. tropicalis provides a powerful tool for recapitulating a perfect regeneration phenomenon, elucidating the underlying molecular mechanisms of cardiac regeneration in an adult heart, and developing an interventional strategy for the improvement in the regeneration of an adult heart, which may be more applicable in mammals than in species with a lower degree of evolution. However, a noninvasive and rapid real-time method that can observe and measure the long-term dynamic change in the regenerated heart in living organisms to monitor and assess the regeneration and repair status in this model has not yet been established. Results In the present study, the methodology of echocardiographic assessment to characterize the morphology, anatomic structure and cardiac function of injured X. tropicalis hearts established by apex resection was established. The findings of this study demonstrated for the first time that small animal echocardiographic analysis can be used to assess the regeneration of X. tropicalis damaged heart in a scar-free perfect regeneration or nonperfect regeneration with adhesion manner via recovery of morphology and cardiac function. Conclusions Small animal echocardiography is a reliable, noninvasive and rapid real-time method for observing and assessing the long-term dynamic changes in the regeneration of injured X. tropicalis hearts.